The effect of foot placement on the jump shot accuracy of NCAA Division I basketball players - Williams, C. Q.; Webster, L.; Spaniol, F.; Bonnette, R. (The Sport Journal, 2016)
The purpose of this study was to investigate the effect of foot placement on the jump shot accuracy of college basketball players. Participants were 11 female NCAA Division I basketball players. The two point shooting protocol adapted from Pojskic, Šeparovic, and Užicanin (2011) was used to identify foot placement and evaluate accuracy for each subject. For each jump shot attempt, foot placement was recorded as either in front (in a dominant staggered stance), even (in a neutral parallel stance), or behind (in a cross-dominant staggered stance). Each attempt was also recorded as either a make or a miss. Descriptive and inferential statistics were used to evaluate the differences in jump shot accuracy for each of the three foot placement positions. A one-way ANOVA staggered stance, shooting accuracy, shooting percentage